Intestinal microbiota profiles associated with low and high residual feed intake in chickens across two geographical locations. - Sina-Catherine Siegerstetter; Stephan Schmitz-Esser; Elizabeth Magowan; Stefanie Urimare Wetzels; Qendrim Zebeli; Peadar G Lawlor; Niamh E O'Connell; Barbara U Metzler-Zebeli (PLoS ONE, 2017)
Intestinal microbe-host interactions can affect the feed efficiency (FE) of chickens. As inconsistent findings for FE-associated bacterial taxa were reported across studies, the present objective was to identify whether bacterial profiles and predicted metabolic functions that were associated with residual feed intake (RFI) and performance traits in female and male chickens were consistent across two different geographical locations. At six weeks of life, the microbiota in ileal, cecal and fecal samples of low (n = 34) and high (n = 35) RFI chickens were investigated by sequencing the V3-5 region of the 16S rRNA gene. Location-associated differences in α-diversity and relative abundances of several phyla and genera were detected. RFI-associated bacterial abundances were found at the phylum and genus level, but differed among the three intestinal sites and between males and females. Correlation analysis confirmed that, of the taxonomically classifiable bacteria, Lactobacillus (5% relative abundance) and two Lactobacillus crispatus-OTUs in feces were indicative for high RFI in females (P < 0.05). In males, Ruminococcus in cecal digesta (3.1% relative abundance) and Dorea in feces (<0.1% relative abundance) were best indicative for low RFI, whereas Acinetobacter in feces (<1.5% relative abundance) related to high RFI (P < 0.05). Predicted metabolic functions in feces of males confirmed compositional relationships as functions related to amino acid, fatty acid and vitamin metabolism correlated with low RFI, whereas an increasing abundance of bacterial signaling and interaction (i.e. cellular antigens) genes correlated with high RFI (P < 0.05). In conclusion, RFI-associated bacterial profiles could be identified across different geographical locations. Results indicated that consortia of low-abundance taxa in the ileum, ceca and feces may play a role for FE in chickens, whereby only bacterial FE-associations found in ileal and cecal digesta may serve as useful targets for dietary strategies.